Pemaknaan Generasi Z terhadap Lagu “Akad” Karya Payung Teduh: Analisis Resepsi Stuart Hall - Muhammad Luthfie; Zahra Karina Restu Wijaya; Agustini Agustini (Institut Nalanda, 2026)
This study examines how Generation Z interprets the song “Akad” by Payung Teduh through the perspective of Stuart Hall’s reception theory. The development of digital media, especially YouTube, has influenced how music is consumed and understood, particularly among Generation Z, who tend to use music as a medium for emotional expression and meaning-making. The song “Akad” is widely recognized for its simple yet meaningful portrayal of love, commitment, and long-term relationships, making it relevant to explore how audiences construct its meaning. This study aims to analyze the interpretation of Generation Z toward the song’s lyrics and to identify the factors that shape their understanding of love expectations. Using a qualitative approach with reception analysis, data were collected through in-depth interviews with Generation Z informants in Bogor City. The findings reveal that audience interpretations vary across three reception positions: dominant, negotiated, and oppositional. Most informants are positioned within the negotiated reading, where they accept the general message of the song while adjusting it based on their personal experiences and social realities. These results indicate that Generation Z actively engages in interpreting media messages rather than passively receiving them. This study highlights that music serves not only as entertainment but also as a medium that shapes emotional understanding, expectations, and perspectives on romantic relationships in the digital era.